2021
DOI: 10.1007/s11469-021-00590-3
|View full text |Cite|
|
Sign up to set email alerts
|

Problematic Online Behaviors Among Gamers: the Links Between Problematic Gaming, Gambling, Shopping, Pornography Use, and Social Networking

Abstract: The aim of the current study was to investigate how problematic online gaming, problematic online gambling, problematic online shopping, problematic online pornography use, and problematic online social networking are associated with each other in bivariate and multivariate, network analytic analyses in an international gamer population. The effective sample comprised 4,416 gamers (age M = 23.31, SD = 6.72; 94% male). Participants filled out the specific problematic Internet use scales on gaming, gambling, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…Aside of the taxonomical implications highlighted above, our findings have practical implications in relation to the assessment and intervention protocols related to addictive disorders ( Burleigh et al, 2019 , Demetrovics and Griffiths, 2012 , Griffiths, 1996 , Griffiths, 2005 , Griffiths, 2017 ). Firstly, considering assessment, the present study highlights the need for less broadly accepted forms of addictive problematic behaviors such as exercise, shopping, internet use and social media to be separately assessed in clinical practice ( Andreassen et al, 2015 , Rozgonjuk et al, 2021 , Stavropoulos et al, 2013 , Trot et al, 2020 ). It is important to note, that some of the addictive behaviors analyzed in the current study are yet to be formally recognized as such (i.e., social media abuse, compulsive shopping, disordered internet use, and hypersexual activity).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Aside of the taxonomical implications highlighted above, our findings have practical implications in relation to the assessment and intervention protocols related to addictive disorders ( Burleigh et al, 2019 , Demetrovics and Griffiths, 2012 , Griffiths, 1996 , Griffiths, 2005 , Griffiths, 2017 ). Firstly, considering assessment, the present study highlights the need for less broadly accepted forms of addictive problematic behaviors such as exercise, shopping, internet use and social media to be separately assessed in clinical practice ( Andreassen et al, 2015 , Rozgonjuk et al, 2021 , Stavropoulos et al, 2013 , Trot et al, 2020 ). It is important to note, that some of the addictive behaviors analyzed in the current study are yet to be formally recognized as such (i.e., social media abuse, compulsive shopping, disordered internet use, and hypersexual activity).…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, research supports that predisposing factors such as depression ( Xu et al, 2020 ), anxiety ( Stavropoulos et al, 2017 ), maladaptive strategies ( Ostovar et al, 2021 ), and adverse life experiences ( Farré et al, 2015 ), may act as antecedents leading to the development and maintenance of co-occurring addictive behaviors (see also the I-PACE model explaining the rise of addictive behaviors, in particular in the online realm; Brand et al, 2016 , Brand et al, 2019 ). Similarly, evidence indicates that commonalities across forms of addictions might act as a ‘gateway’ increasing the likelihood of comorbid addictions ( Burleigh et al, 2019 , Rozgonjuk et al, 2021 ). For example, Delfabbro and King (2020) suggest that the ‘digital convergence’ of certain online activities facilitates the comorbid presentations of addictions in online environments (i.e., gambling, gaming, disordered internet use, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Given the rise in popularity of gaming in today’s society, a key area of research within psychology and psychiatry is related to the potential positive (see Griffiths ( 2019 ) and Mandryk et al ( 2020 )) and negative effects stemming from electronic games, with several studies reporting a wide range of detrimental effects elicited by video game play behaviors, such as aggression (Lemmens et al, 2011 ; López-Fernández et al, 2020 ), addiction (Pontes, 2018 ; Pontes & Griffiths, 2014 ), and other resulting psychiatric comorbidities (Pontes, 2018 ; Sherry, 2001 ), including but not limited to attention-deficit/hyperactivity disorder (ADHD) (Stavropoulos et al, 2019 ), autism spectrum disorders (ASD) (Craig et al, 2021 ), and depression (Ostinelli et al, 2021 ), among other behavioral addictions (Rozgonjuk et al, 2021 ), with recent evidence linking disordered gaming with poor physical health through impaired psychological well-being (Moore et al, 2021 ).…”
mentioning
confidence: 99%
“…In general, online addiction problems yielded small to high positive bivariate correlations (between r = 0.15 and r = 0.57), which is higher than those indicated in previous studies [ 3 , 25 ], except for GIA and online gambling addiction, as well as gaming and social networking addictions, for which the present study did not find an association. A recent study focused on gaming found internet-based problematic behaviours were separate entities [ 26 ]. Therefore, in CBT applied to GIA, comorbidity with other psychopathology and other online problems should be assessed and potentially prioritised depending on the respective client’s individual problem constellations [ 8 ], as relieving emotional distress can indirectly reduce problematic internet use [ 6 ].…”
Section: Discussionmentioning
confidence: 99%